ContactLess Integrated Photonic Probe for light monitoring in indium phosphide‐based devices. Issue 4 (1st August 2015) - Melati, Daniele; Carminati, Marco; Grillanda, Stefano; Ferrari, Giorgio; Morichetti, Francesco; Sampietro, Marco; Melloni, Andrea
Abstract : The increasing complexity of photonic integrated circuits requires the possibility to monitor the state of the circuit in order to stabilise the working point against environmental fluctuations or to perform reliable reconfiguration procedures. Although indium phosphide (InP) technologies can naturally integrate high‐quality photodiodes, their use as tap monitors necessarily affects the circuit response and is restricted to few units per chip. Transparent power monitors are hence key components for complex circuits. In this study, the authors present the implementation of a ContactLess Integrated Photonic Probe (CLIPP) realising a non‐invasive integrated light monitor on InP‐based devices. They describe an innovative vertical scheme of the CLIPP monitor which exploits the back side of the chip as a common electrode, thus enabling a reduction of the device footprint and a simplification of the electrical connectivity. They characterise the response of the CLIPP and demonstrate its functionality as power monitor. Lastly, they provide a direct demonstration that CLIPP monitor allows accessing more accurate information on the working point of photonic integrated circuits compared with conventional external or integrated photodetectors.